CO-ADMINISTRATION OF GOKO HERBAL CLEANSER AND PARACETAMOL: A HERB-DRUG INTERACTION STUDY - Amadi, Cecilia Nwadiuto; Edevbie, Oghenetega Ruth (Universal Journal of Pharmaceutical Research, 2021)
Aim: The present study aimed to evaluate the effects of co-administering paracetamol and Goko cleanserâon the liver. Method: Twenty rats divided into four different groups were used for this Study. Group one (control group) received distilled water only; Group two received paracetamol only (100mg/kg), Group three received Goko cleanserâonly (2 mL/kg) and Group four received paracetamol and Goko cleanserâconcomitantly for 3 days. Blood and liver samples were analyzed for biochemical and histopathological parameters respectively. Results: Data obtained revealed a significant decrease (p<0.05) in the levels of the liver enzymes (ALT, AST, and GGT) in the Goko cleanserâ-only group compared to control. A significant decrease in AST was also observed in paracetamol + Goko cleanserâgroup. No significant change in ALT, ALP and GGT levels in the paracetamol + Goko cleanserâgroups was observed. Results of histology examination showed normal liver tissues with normal hepatocytes, sinusoids and central vein for both treated and control groups. Conclusion: The significant reductions in the liver enzymes by observed in the Goko cleanserâ-only group indicated potential hepato-protective effects which could be due to the presence of phenolic compounds which acted as antioxidants. The short-term co-administration of paracetamol and Goko cleanserâproduced no liver toxicity. However, this is subject to further studies using pharmacokinetic analysis and also, a long-term study is strongly advocated. Peer Review History: Received: 4 June 2021; Revised: 7 July; Accepted: 13 August; Available online: 15 September 2021 Academic Editor: Essam Mohamed Eissa , Beni-Suef University, Egypt, dressamceutics@yahoo.com Reviewers: Ahmad Najib , Universitas Muslim Indonesia, Makassar, Indonesia, ahmad.najib@umi.ac.id Dr. Dennis Amaechi , MrsFoluBabade Mini Estate , Flat 5 by Old Soldiers Quarter, Sabongari/Bwari, Abuja- Federal Capital Territory, Nigeria. amaechitoexcel@yahoo.com Dr. Sangeetha Arullappan , Universiti Tunku Abdul Rahman, Malaysia, sangeetha@utar.edu.my Taha A.I. El Bassossy , Medicinal and Aromatic Plants Department, Desert Research Center, Cairo, Egypt, tahachemist2008@gmail.com